2022
DOI: 10.1039/d2tc01812h
|View full text |Cite
|
Sign up to set email alerts
|

Splendid four-mode optical thermometry design based on thermochromic Cs3GdGe3O9:Er3+ phosphors

Abstract: Optical thermometry has emerged as an inspiring area taking account of its unique advantages including contactless operation, rapid response time, excellent spatial resolution, and wide detection range. However, most current...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 53 publications
(107 reference statements)
0
18
0
Order By: Relevance
“…27 Moreover, Guo et al demonstrated that CGG host UCL phosphors have a good application in temperature sensing. 28,29 Based on the above studies, we believe that CGG host has the characteristics of drastically changing the Er 3+ -Yb 3+ distance by temperature, possibly generating host defects, and having phonon-assisted transitions. Therefore, CGG is selected as the research target to achieve thermal enhancement and can be used as photothermal sensing under high temperature.…”
Section: Introductionmentioning
confidence: 85%
“…27 Moreover, Guo et al demonstrated that CGG host UCL phosphors have a good application in temperature sensing. 28,29 Based on the above studies, we believe that CGG host has the characteristics of drastically changing the Er 3+ -Yb 3+ distance by temperature, possibly generating host defects, and having phonon-assisted transitions. Therefore, CGG is selected as the research target to achieve thermal enhancement and can be used as photothermal sensing under high temperature.…”
Section: Introductionmentioning
confidence: 85%
“…In addition to adjusting the power density and pulse width of the 980 nm laser, the ambient temperature of the phosphor also greatly affects its emission color. 30 Temperature-dependent contour mapping of UC spectra for the Sr 2 InF 7 : 2%Yb 3+ , 2%Er 3+ phosphor is displayed in Figure 5a, in which the green emission intensity was always much higher than the red emission intensity, and the value of R/G changed little in the 300−480 K temperature range (Figure 5b). This result meant that the emission color of the present sample was almost unaffected by environmental temperature.…”
Section: Green Uc Luminescence Under Differentmentioning
confidence: 99%
“…31 Besides, Wei et al reported the non-concentration quenching of the Cs 3 GdGe 3 O 9 :Er 3+ phosphor and successfully applied it to optical thermometers. 32 Here, we synthesized Bi 3+ /Eu 3+ -doped Cs 3 GdGe 3 O 9 (CGGO) phosphors and investigated their photoluminescence properties. The ET mechanism and temperature-dependent luminescence of Cs 3 GdGe 3 O 9 : Bi 3+ ,Eu 3+ were investigated.…”
Section: Introductionmentioning
confidence: 99%